I need to show how I worked out the solution Nov 5 | Nick from Boston, MA | 2 Answers | 0 Votes Mark favorite Subscribe Comment
Multiply the first equation by 2, subtract the second equation from it, divide the result by 5: (8x+6y+14m)=23 -(3x+y+9m)=-10 5x+5y+5m=13 x+y+m=13/5. Nov 5 | Andre W. Comment
From the second equation y=10-3x-9m; Plug it into the first equation to get: 4x+3(10-3x-9m)+7m=-5x-20m+30=11.5 From this we obtain upon simplification: x+4m=3.7 Thus x=3.7-4m; Plug it in the expression for y to obtain: y=10-3x-9m=10-3(3.7-4m)-9m=-1.1+3m So, we have: y=3m-1.1 x=-4m+3.7 Therefore, x+y+m=3m-1.1-4m+3.7+m=2.6 Nov 5 | Kirill Z. Comment